Do speed cameras reduce road traffic collisions? - Graham,D; Niak,C; McCoy,EJ; Li,H (PLoS One, 2019)
This paper quantifies the effect of speed cameras on road trafficcollisions using anapproximate Bayesian doubly-robust (DR) causal inference estimation method.Previous empirical work on this topic, which shows a diverse range ofestimatedeffects, is based largely on outcome regression (OR) models using the Empirical Bayesapproach or on simple before and after comparisons. Issues of causality andconfounding have received little formal attention. A causal DR approach combinespropensity score (PS) and OR models to give an average treatmenteffect (ATE)estimator that is consistent and asymptotically normal under correct specification ofeither of the two component models. We develop this approach withina novelapproximate Bayesian framework to derive posterior predictive distributions for theATE of speed cameras on road traffic collisions. Our results for England indicatesignificant reductions in the number of collisions at speed cameras sites (mean ATE =-15%). Our proposed method offers a promising approach for evaluation of transportsafety interventions.